Right to be forgotten: the balance between the right to privacy and the freedom of the press - Račiņa, Amanda (Riga Graduate School of Law, 2024)
In the digital era, the right to be forgotten, outlined in Article 17 of the GDPR, allows individuals to request the removal of personal data from online platforms. Initially targeting search engines, this right now extends to journalistic publications online, raising concerns about its impact on press freedom. Balancing privacy rights with freedom of expression, particularly in the digital sphere, poses significant challenges. The expansion of the right to be forgotten requires exploring the balance between protecting individual privacy rights and preserving the freedom of the press. The principal aim of this thesis is to explore how the right to be forgotten coexists with the freedoms of expression, the press, privacy, and data protection.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection; right to be forgotten; freedom of press; General Data Protection Regulation